Pengaruh Natrium Sulfat Terhadap Kerusakan Dan Kekuatan Bending Batu Tempel Berbahan Plastik-Pasir Serta Batu Apung - Ade Antara, I Kadek Riko; Suardana, Ngakan Putu Gede; Kencanawati, Cok Istri Putri Kusuma (Teknik Desain Mekanika, 2022)
Abstract Plastic is an inorganic waste that can cause various environmental problems such as pollution of soil, water and global warming due to the length of time it is decomposed by nature. One way to recycle plastic waste is by chopping and thawing with sand and pumice used as reinforcement. This research used HDPE (High Density Polyethylene) plastic as a binder mixed with sand and pumice as reinforcement in a ratio (1:¹/2 :¹/2) processed into stone paste. Test by immersion with 5%, 10%, and 15% sodium sulfate for 30 days, bending test using ASTM D790-03 guidelines, and micro-photo test. Testing of silakarang sandstone was also carried out as a comparison. The results of the sodium sulfate immersion showed that the higher the percentage, the higher the damage suffered by the specimen, the highest damage occurred in the specimens soaked in 15% sodium sulfate of 2.50%. Data from the bending test results have the highest average of un-soaked paste stone composites, which is 26.71 Mpa and the lowest with 15% sodium sulfate immersion which is 9.61 Mpa. The photo of the results of the micro-photo test can see the morphology of the composite surface, it can be seen that the bond between the particles is the most tightly contained. The results showed that the composite masonry without immersion had the highest value, this indicated that the treatment with sodium sulfate had a bearing on the mechanical strength as seen from the decrease in the bending strength of the specimen. Key Word : Paste stone, Sodium sulfate, Bending test, High Density Polyethylene